The Study of Turn Taking Created in “Cinderella” Movie 2015 - Rachma Nurma Gupita; Katharina Rustipa (Universitas Stikubank (UNISBANK) Semarang, 2021)
This research has two objectives. The first objective is to find the type of turn-taking mechanism in the dialogue of David Barron's